Liver Injury as a Surrogate for Inflammation and Predictor of Outcomes in COVID‐19. Issue 1 (6th October 2020) - Mishra, Kajali; Naffouj, Sandra; Gorgis, Sarah; Ibrahim, Hanan; Gill, Sonika; Fadel, Raef; Chatfield, Abigail; Tang, Amy; Salgia, Reena
Abstract : Respiratory failure is the most common cause of death in patients with corona virus disease 2019 (COVID‐19). There have been many investigations to determine predictors of bad outcomes in patients with this illness. Liver enzyme elevation has been described in hospitalized patients with severe COVID‐19; however, little is known about the significance of liver injury regarding outcomes. We conducted a retrospective chart review of 348 patients admitted with COVID‐19 in our quaternary care center. Liver injury on admission was defined based on the laboratory cutoff of aspartate aminotransferase >35 IU/L and/or alanine aminotransferase >52 IU/L. Patients were divided into two cohorts based on the presence or absence of liver injury. These cohorts were compared to assess differences in presentation, complications, and outcomes. The primary outcome was respiratory failure requiring intubation, and the secondary outcome was in‐hospital mortality. The presence of new onset liver enzyme elevation on presentation was associated with increased severity of illness, need for mechanical ventilation, and mortality. Presence of liver injury increased the chance of acute hypoxic respiratory failure requiring mechanical ventilation by 1.79 times. The degree and timeline of liver enzyme elevation during hospitalization corresponded with elevations of other inflammatory markers. Conclusion : Liver injury appears to correlate with the inflammatory syndrome caused by COVID‐19, with the degree of liver injury corresponding with severity of inflammation. We suggest early and continued monitoring of liver enzymes as they can be useful to identify patients who may need early escalation of care.